2023
DOI: 10.3390/molecules28073036
|View full text |Cite
|
Sign up to set email alerts
|

Selenium Enrichment of the Edible Medicinal Mushroom Antrodia camphorata by Submerged Fermentation

Abstract: Selenium (Se) is an essential nutrient element in human physiological metabolism and immune function. Supplementation of bioavailable Se will confer benefit on human life, especially when intake of this nutrient is inadequate. The edible and medicinal mushroom Antrodia camphorata is a unique fungus endemic to Taiwan, which has shown high therapeutic and nutritive value. This study is the first to demonstrate that A. camphorata can assimilate and transform sodium selenite into organic selenium. With an initial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Microscopic findings revealed that 10 µM of both isolated constituents inhibited the formation of visible cytopathic effects, with IC 50 values lower than that of Oseltamivir (61 and 52 µM respectively compared to 64 µM), suggesting the potential of T. linteus -derived constituents as stronger neuraminidase inhibitors of Influenza A H1N1 virus than the commonly used Oseltamivir treatment [ 13 ]. In addition, recent findings by Li et al [ 35 , 38 ] reported that hispidin and hypholomine B from the mycelial ethanol extract of T. linteus reduced the expression of angiotensin-converting enzyme 2 (ACE2) gene in HepG2 cells and blocked the spike receptor-binding domain to minimize the entry of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) virus, further demonstrating the strong antiviral and therapeutic potential of T. linteus for viral infections.…”
Section: Health-promoting Propertiesmentioning
confidence: 91%
See 1 more Smart Citation
“…Microscopic findings revealed that 10 µM of both isolated constituents inhibited the formation of visible cytopathic effects, with IC 50 values lower than that of Oseltamivir (61 and 52 µM respectively compared to 64 µM), suggesting the potential of T. linteus -derived constituents as stronger neuraminidase inhibitors of Influenza A H1N1 virus than the commonly used Oseltamivir treatment [ 13 ]. In addition, recent findings by Li et al [ 35 , 38 ] reported that hispidin and hypholomine B from the mycelial ethanol extract of T. linteus reduced the expression of angiotensin-converting enzyme 2 (ACE2) gene in HepG2 cells and blocked the spike receptor-binding domain to minimize the entry of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) virus, further demonstrating the strong antiviral and therapeutic potential of T. linteus for viral infections.…”
Section: Health-promoting Propertiesmentioning
confidence: 91%
“…Besides that, T. camphoratus mycelium extract recorded strong and dose-dependent scavenging activity, which can be attributed to its high phenolic content, observed to be at 20 mg/g [ 14 ]. Furthermore, Li et al [ 35 ] reported that the polysaccharides isolated from T. camphoratus which were enriched with selenium recorded almost double the DPPH and ABTS radical scavenging activity in comparison to the unenriched polysaccharides, thus suggesting the possibility of raising the antioxidant properties of T. camphoratus through modifications of isolated bioactive compounds.…”
Section: Health-promoting Propertiesmentioning
confidence: 99%